2019
DOI: 10.3390/jcs3020032
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Molecular Dynamics Study of the Thermal Decomposition of Phenolic Resins

Abstract: The thermal decomposition of polyphenolic resins was studied by reactive molecular dynamics (RMD) simulation at elevated temperatures. Atomistic models of the polyphenolic resins to be used in the RMD were constructed using an automatic method which calls routines from the software package Materials Studio. In order to validate the models, simulated densities and heat capacities were compared with experimental values. The most suitable combination of force field and thermostat for this system was the Forcite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…At present, the research work on phenolic resin mainly focuses on chemical modification and the synthesis process, while the thermal degradation study of modified phenolic resin has been less reported. As an important thermal protective ablation material substrate, the degradation properties of modified phenolic are closely related to its application under a high-temperature ablation environment [21]. On the other hand, the degradation study of the modified phenolic resin can provide rational feedback for the modification of the resin.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research work on phenolic resin mainly focuses on chemical modification and the synthesis process, while the thermal degradation study of modified phenolic resin has been less reported. As an important thermal protective ablation material substrate, the degradation properties of modified phenolic are closely related to its application under a high-temperature ablation environment [21]. On the other hand, the degradation study of the modified phenolic resin can provide rational feedback for the modification of the resin.…”
Section: Introductionmentioning
confidence: 99%
“…The MD and GCMC simulations in this paper were realized on the Materials Studio molecular simulation software 34,35 , which offers a rich set of features for materials modeling. In the simulation, MD and GCMC had adopted the COMPASS force field 36,37 to describe the inter-atom interactions, the Ewald method was employed to manage the long-range electrostatic interaction between particles, and the periodic boundary conditions were applied in the X, Y and Z directions of the simulation box [38][39][40] .…”
Section: Methodsmentioning
confidence: 99%
“…The structure was relaxed with a short period of MD between reaction steps. After many iterations, a cured polymer structure was obtained [43] (Fig. 3 is an example of the structures generated).…”
Section: Methodsmentioning
confidence: 99%